A report on the online learning experience of students in accounting course. (2015) - Lam, Jeanne Y.C.; Chan, Radar K.H.; Yan, Kennis Y.K.
Blended learning, the incorporation of different learning environments, is widely adopted in higher education institutions. The term usually refers to the combination of traditional face-to-face classroom methods with modern computer-mediated activities. Through a blended learning approach, online learning plays an important role in the learning process which allows learning to happen at anytime, anywhere. The purpose of this paper is to investigate the online learning experience of students in a blended learning based course. A quantitative methodology was adopted in this research. A survey was conducted to collect students' experience and perception of various online course materials after taking the three-month course. Questions about online course design, online course materials and online learning experience were asked. The results show that most of the students were satisfied with the provision of online course materials which made their study more flexible and accessible. The accounting course was specially designed such that online activities and assessment tasks were aligned to the intended learning outcomes, in order to help students' study and enhance their learning experience. Furthermore, it was found that students preferred having more types of online learning materials and mobile learning support. The study on blended learning in accounting is very limited in Hong Kong. The value of this paper is to fill this gap in the literature. The paper examines the online learning experience of students in accounting which can be served as a reference for online learning development in this subject area in the future.